2 . 3 2 + 0 . 6 9 + 0 . 0 9 2 . 3 3 − 0 . 0 2 7
Quick! Calculate the expression above as fast as possible! Time is of the essence!
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes correct! Note that one can generalize this: a 3 − b 3 = ( a − b ) ( a 2 + a b + b 2 ) , so a − b = a 2 + a b + b 2 a 3 − b 3 . In this case, we have a = 2 . 3 , b = 0 . 3 .
Problem Loading...
Note Loading...
Set Loading...
It should have been:
2 . 3 2 + 0 . 6 9 + 0 . 0 9 2 . 3 3 − 0 . 0 2 7
= 2 . 3 2 + 0 . 6 9 + 0 . 0 9 ( 2 . 3 3 − 0 . 3 3 )
= 2 . 3 2 + 0 . 6 9 + 0 . 0 9 ( 2 . 3 − 0 . 3 ) ( 2 . 3 2 + 0 . 6 9 + 0 . 0 9 )
= 2 . 3 − 0 . 3 = 2